The transient intraluminal filament middle cerebral artery occlusion model as a model of endovascular thrombectomy in stroke - Sutherland, B; Neuhaus, A; Couch, Y; Balami, J; De Luca, G; Hadley, G; Harris, S; Grey, A; Buchan, A (SAGE Publications, 2015)
The clinical relevance of the transient intraluminal filament model of middle cerebral artery occlusion (tMCAO) has been questioned due to distinct cerebral blood flow profiles upon reperfusion between tMCAO (abrupt reperfusion) and alteplase treatment (gradual reperfusion), resulting in differing pathophysiologies. Positive results from recent endovascular thrombectomy trials, where the occluding clot is mechanically removed, could revolutionize stroke treatment. The rapid cerebral blood flow restoration in both tMCAO and endovascular thrombectomy provides clinical relevance for this pre-clinical model. Any future clinical trials of neuroprotective agents as adjuncts to endovascular thrombectomy should consider tMCAO as the model of choice to determine pre-clinical efficacy.